Handball performane - Cardinale, M. (2015)
In this Aspetar Tuesday Scientific Lecture, Dr Marco Cardinale gives an overview of handball. He explains the standard match, the physical characteristics of the players, the game demands and evolution, training aspects, common injuries and gives advice on nutrition for players.